Optimalisasi Evaluasi dalam Meningkatkan Kualitas Pengelolaan Pendidikan Di SDN 16 Lintang Kanan - Pebri Yanti; Aprilia Fitrotun; Ilham Syukri; Ainul Fitri (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: Evaluation in education management has not been optimally carried out, because there are still some schools that have not been evaluated optimally, resulting in poor quality education management. The purpose of this research is to map and evaluate the optimization of evaluation in improving the quality of education management at SDN 16 Lintang Kanan. Using a qualitative descriptive method, with the CIPP model approach (Context, Input, Process and Product). Information obtained through observation, interviews, and documentation. The results of the study concluded that management at the Contex level had carried out planning, organizing, actuating and controlling. The input level includes students, curriculum, teaching materials, and human resources, financing and educational infrastructure. The process level is directly related to educational activities, the use of learning media, the use of facilities and infrastructure and the assignment of types of assignments. As well as from product/output assessments related to the results of the implementation of education management where the research results show that the output of education management is good and the results are visible.Keywords: Optimization, Evaluation, Quality of Education Management Abstrak: Evaluasi dalam pengelolaan pendidikan belum optimal dilakukan, karena masih terdapat sebagian sekolah belum dilakukan evaluasi secara optimal sehingga mengakibatkan pengelolaan pendidikan belum berkualitas. Tujuan dari penelitian ini untuk memetakan dan mengevaluasi optmalisasi evaluasi dalam meningkatkan kualitas pengelolaan pendidikan di SDN 16 Lintang Kanan. Menggunakan metode deskriptif kualitatif, dengan pendekatan model CIPP (Conteks, Input, Proses dan Produk). Informasi diperoleh melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menyimpulkan bahwa pengelolaan pada tingkat Contex telah dilaksanakan planning, organizing, actuating dan controlling. Tingkat input meliputi peserta didik, kurikulum, bahan ajar, dan sumber daya manusia, pembiayaan serta sarana prasarana pendidikan. Tingkat proses berkaitan langsung dengan, aktivitas pendidikan, penggunaan media pembelajaran, kemanfaatan sarana dan prasarana dan pemberian jenis tugas. Serta dari penilaian produk/output yang berhubungan dengan hasil pelaksanaan pengelolaan pendidikan dimana hasil penelitian menunjukkan bahwa output dari pengelolaan pendidikan sudah baik dan Nampak hasilnya.Kata Kunci: Optimalisasi, Evaluasi, Kualitas Pengelolaan Pendidikan